Cuproptosis-related gene signatures define immune subtypes and predict prognosis in gastric cancer - Wang, Zhe; Man, Yuxin; Yue, Bingtong; Liu, Min; Zhang, Jiayi; Wang, Feng; Xin, Dao (Frontiers in Molecular Biosciences, 2026)
IntroductionDespite recent improvements in diagnostic and therapeutic strategies, gastric cancer (GC) continues to be a major contributor to global cancer fatalities, resulting in suboptimal patient prognosis overall. Cuproptosis, defined as a regulated death mode initiated by intracellular copper overload, has not been comprehensively examined in the context of the tumor immune microenvironment or its prognostic relevance in stomach adenocarcinoma.MethodsComprehensive transcriptomic analyses of TCGA and GEO cohorts were performed to identify cuproptosis-related molecular subtypes and to develop a prognostic risk model based on cuproptosis-associated genes. Correlations between the risk score and features of the TIME were thoroughly evaluated. RT-qPCR was conducted in 14 paired gastric tumor and adjacent normal tissues to validate the expression of key prognostic genes.ResultsThree distinct cuproptosis-associated molecular subtypes were identified in STAD. A five-gene prognostic signature—PEG10, RPL39L, MMP11, SYNPO2, and KRT17—was established, which showed strong associations with overall survival and multiple immunological indicators, including immune cell infiltration, MSI, TMB, immune checkpoint expression, and HLA profiles. Subsequently, a nomogram provided enhanced individualized survival prediction.ConclusionThe identified cuproptosis-related gene signature is associated with the immunological heterogeneity of gastric cancer. Together, these results point to previously unrecognized links between cuproptosis and antitumor immunity, may provide insights for refining immunotherapeutic strategies in gastric cancer. Continued experimental investigation will be necessary to unravel how cuproptosis contributes to gastric cancer development and to validate its association with immune regulation.